INCREASING RED CHILLI PLANT PRODUCTIVITY THROUGH OPTIMAL FERTILIZATION MANAGEMENT: PENINGKATAN PRODUKTIVITAS TANAMAN CABAI MERAH MELALUI MANAJEMEN PEMUPUKAN YANG OPTIMAL - Aulia, Tia (LPPM UPMI, 2024)
The productivity of red chili plants (Capsicum annuum L.) is a key factor in the successful cultivation of this horticultural commodity. Although the demand for red chili continues to increase, its productivity is still not optimal in various regions, which is largely due to inappropriate fertilization management. This study aims to examine and identify optimal fertilization management strategies to increase the productivity of red chili plants. Through the literature study method, this study analyzed various literature discussing the types of fertilizers, doses, application times, and effective fertilization techniques for red chili plants. The results of the analysis show that the use of fertilizers that are appropriate to plant needs, combined with appropriate application techniques, can significantly increase the growth and yield of red chili. This study concludes that optimal fertilization management, which includes selecting the right type of fertilizer, appropriate dose, and effective application time, is an important factor in increasing the productivity of red chili plants. The recommendations generated from this study are expected to be a practical guide for farmers in their efforts to increase the yield of red chili cultivation sustainably and efficiently.